2015
DOI: 10.1002/ep.12101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the oxidation reaction parameters of different carbon structure particles

Abstract: This study explores the effect of the difference in the carbon structure of particles on their reactivity towards O2. Particles with three types of carbon structures were captured in the exhaust of a diesel engine fueled with blends of diesel with 0, 5, and 15 vol % methanol (designated here as M0, M5, and M15). The Raman spectra were used to designate the particles as a high graphitization structure (L1), a secondary graphitization structure (L2), or a low graphitization structure (L3) according to the carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Zhao et. al [43] showed that D3 band FWHM of biodiesel PM increased with biodiesel content. D1 band FWHM, I D1 /I G and A D1 /A G showed reverse relations with t 50% (time corresponding to 50% mass loss) for soot from different sources, and G FWMH was almost the same [21].…”
Section: Resultsmentioning
confidence: 97%
“…Zhao et. al [43] showed that D3 band FWHM of biodiesel PM increased with biodiesel content. D1 band FWHM, I D1 /I G and A D1 /A G showed reverse relations with t 50% (time corresponding to 50% mass loss) for soot from different sources, and G FWMH was almost the same [21].…”
Section: Resultsmentioning
confidence: 97%
“…This will result in a higher maximum combustion temperature in the cylinder than when the exhaust gas is introduced. When the oxygen concentration in the cylinder is low, the condition is favorable for the formation and growth of particles , eventually leading to increases in the size, quantity, and mass concentration of particle emissions. However, compared with exhaust gas and N 2 , on the one hand CO 2 has a higher heat capacity value, which can significantly reduce the maximum combustion temperature in the cylinder and has the effect of inhibiting particle formation.…”
Section: Discussionmentioning
confidence: 99%
“…C b was used to evaluate the burnout performance of the PM samples, and was defined as follows (Zhao et al, 2015):…”
Section: Burnout Characteristic Indexmentioning
confidence: 99%